Investigations of the high temperature gas-cooled reactors fuel in the world - Dyussambayev, D.S.; Gizatulin, Sh.Kh.; Shaimerdenov, A.A.; Chekushina, L.V.; Burtebayev, N.T. (Recent Contributions to Physics, 2018)
The high-temperature gas-cooled reactor has increased safety, self-protection and virtually eliminates such a serious accident as the core meltdown, and also belongs to the fourth-generation power systems. In many countries, research, development and engineering studies of fuel, technology and design of the HTGR are conducted. In Kazakhstan, it is planned to build a nuclear power plant. One of the applicants is a station based on the HTGR. The RSE “Institute of Nuclear Physics” of the Ministry of Energy of the Republic of Kazakhstan, together with the Agency of Atomic Energy of Japan, conducts researches on fuel and materials of the HTGR. This paper provides an overview of the current state of researches of a high-temperature gas-cooled reactor in the world, including the results of resource tests of three structural isotropic fuels of a high-temperature gas-cooled reactor before burning out at 90 GW d / t under operating conditions of HTGR in the core of the WWR-K research reactor. The fuel is coated with two layers of pyrolytic carbon and a layer of silicon carbide. During the irradiation, the gaseous fission products formed were monitored. One of the main tasks of these studies is the development of fuel, which will maintain the maximum integrity of the shell with its deep burnout.